2019
DOI: 10.1016/j.nbd.2018.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Decreased circulating ErbB4 ectodomain fragments as a read-out of impaired signaling function in amyotrophic lateral sclerosis

Abstract: ErbB4 is a transmembrane receptor tyrosine kinase that binds to neuregulins to activate signaling. Proteolytic cleavage of ErbB4 results in release of soluble fragments of ErbB4 into the interstitial fluid. Disruption of the neuregulin-ErbB4 pathway has been suggested to be involved in the pathogenesis of amyotrophic lateral sclerosis (ALS). This study assesses whether soluble proteolytic fragments of the ErbB4 ectodomain (ecto-ErbB4) can be detected in cerebrospinal fluid (CSF) and plasma, and if the levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…It is tempting to speculate that serum ERBB4 levels could be a biomarker for mitochondrial dysfunction in skeletal muscle in DMD. This is further supported by a recent study showing that decreased levels of circulating of ERBB4 ectodomain is strongly associated with impaired ERBB4 pathway in cerebrospinal fluid and plasma of ALS patients ( 43 ). ERBB4 is also highly expressed in smooth muscle as is dystrophin, while smooth muscle lacks dystrophin in DMD.…”
Section: Discussionsupporting
confidence: 71%
“…It is tempting to speculate that serum ERBB4 levels could be a biomarker for mitochondrial dysfunction in skeletal muscle in DMD. This is further supported by a recent study showing that decreased levels of circulating of ERBB4 ectodomain is strongly associated with impaired ERBB4 pathway in cerebrospinal fluid and plasma of ALS patients ( 43 ). ERBB4 is also highly expressed in smooth muscle as is dystrophin, while smooth muscle lacks dystrophin in DMD.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, myotube and MN co-cultures derived from FUS -ALS patient iPSCs showed impaired endplate maturation, and FUS mutant mice had decreased endplate surface area [ 230 ]. Besides, the neurotrophic factor neuroregulin 1 ( NRG-1 ) participates in NMJ maintenance and AchR stability, and Nrg-1-ErbB4 receptor signaling alterations may be involved in the pathogenesis of ALS [ 304 ]. In mutant Sod1 mice, adenoviral overexpression of Nrg-1 by intramuscular adenoviral injection prevented denervation, activated collateral reinnervation, and stabilized AChR clusters through ErbB receptor activation [ 305 ].…”
Section: The Neuromuscular Junction In Alsmentioning
confidence: 99%
“…Importantly, loss-of-function mutations of NRG1 receptor ErbB4 cause a form of late-onset, autosomaldominant ALS in human patients [24]. Furthermore, we recently reported that ErbB4 ectodomain fragments were reduced in cerebrospinal fluid and plasma of ALS patients, indicating an impairment of the NRG1-ErbB signaling [25]. Also, in SOD1 G93A mice and in ALS patients, spinal cord microglial cells express the activated form of ErbB2 receptor and there are enhanced levels of NRG1 in microglial cells [23].…”
Section: Introductionmentioning
confidence: 99%